Brian Castro's Tokyo: Schizophrenic Semiotic (Journal of the Association for the Study of Australian Literature, 2013)
The article argues that Brian Castro's novel Stepper is interested in the 'space of literature' or Blanchot's 'the nowhere which is here', evident in its depiction of Tokyo.